Lipid profile level in oral cancer and its significance on histological grade - Mahasweta Mallik; Sujata Mallick; Manish Kumar; Naveen Kumar Bariar (International Journal of Medical Research and Review, 2016)
Introduction: Oral cancer is one of the commonest cancer in India. Its early detection can prevent morbidity and motality. Aim of this study is to estimate the lipid profile level in oral cancer and its significance on histopathological grade.Material and method: 70 patients with established oral squamous cell carcinoma were taken in the study and their lipid profile analysed.Result: lipid profile had an inverse relationship with oral cancer with no significant relation with histopathological grade.Conclusion: lipid profile estimation is a cost effective method to detect oral cancer.